Volatile compounds and odor traits of dry-cured ham (Prosciutto crudo) irradiated by electron beam and gamma rays. (January 2017) - Kong, Qiulian; Yan, Weiqiang; Yue, Ling; Chen, Zhijun; Wang, Haihong; Qi, Wenyuan; He, Xiaohua
Abstract: Prosciutto crudo samples were irradiated at 0, 3 and 6 kGy by gamma rays (GR) and electron beam (EB), respectively. The odor scores and volatile compounds were examined after 7 days storage at 4 °C. Volatile compounds from samples without and with irradiation at 6 kGy were analyzed by GC–MS. Fifty-nine compounds were identified, including terpenes, aldehydes, alcohols, ketones, alkanes, esters, aromatic hydrocarbons and acids. Both GR and EB irradiation resulted in formation of (Z)-7-Hexadecenal, cis-9-hexadecenal, tetradecane, E-9-tetradecen-1-ol formate, and losing of hexadecamethyl-heptasiloxane and decanoic acid-ethyl ester in hams. However, GR irradiation caused additional changes, such as formation of undecane and phthalic acid-2-cyclohexylethyl butyl ester, significantly higher level of 1-pentadecene, and losing of ( E, E )-2, 4-decadienal and octadecane. EB was shown to be better in maintaining ham's original odor than GR. Our results suggest that EB irradiation is a promising method for treatment of ready to eat hams as it exerts much less negative effect on the flavor of hams compared to GR irradiation. Highlights: The effects of gamma rays and electron beam irradiation on odor traits and volatile compounds of dry-cured hams were analyzed. Electron beam is better in maintaining ham odor than gamma rays at same doses. Both gamma rays and electron beam irradiation at dose of 6 kGy lead to the development of off-odors in hams. Gamma rays irradiation at dose of 6 kGy results in additional volatile compounds changes and worse odor.